Fatores psicossociais e laborais associados ao risco de suicídio entre enfermeiros e médicos da área hospitalar - Freire, Fernanda de Oliveira (2019)
Objective: To analyze the psychosocial and labor factors associated with the risk of suicide among nurses and physicians in the hospital area. Method: This is a cross-sectional study, developed at a University Hospital in Cuiabá-MT, with 216 health professionals, from July and September 2018. The instruments used for data collection were: a questionnaire with sociodemographic, economic, labor and suicidal behavior-related variables; the Mini International Neuropsychiatric Interview (MINI), which evaluated the risk of suicide; the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST); and the Depression, Anxiety and Stress Scale (DASS-21), which verified the presence of such symptoms. We used the SPSS statistical software, version 20.0, to perform bivariate and multiple analyses. The study was approved by the Research Ethics Committee of the Júlio Müller University Hospital (HUJM) under opinion no 2.744.116. Results: The discoveries were displayed in the form of a manuscript with the following characterization of the professionals: predominance the age group from 39 to 59 years (57.87%), female gender (68.06%), heterosexual sexual orientation (95.83%), marital status committed (73.61%), Catholics (59.26%) and family income higher than 20 minimum wages (50.93%). Regarding the labor variables, most had a graduate course (99.07%), and they were physicians (60.65%), worked in the health care sector (91.20%), service time in HUJM less than five years (69.44%), weekly workload equal to or less than 24 hours (54.17%), day shift (78.70%) and with two or more employment bonds (59.26%). The results signalized previous attempted suicides among professionals (5.09%), where the most used methods were medicine overdoses (4.17%) and firearms (0.92%). Attempted suicide and suicide rates were 23.61% and 15.28% among relatives; and attempted suicide and suicide rates were 43.5% and 35.6% among friends. As for the use of psychoactive substances, we noted a high/moderate risk for alcohol (9.72%) and sedatives/hypnotics (5.09%). With respect to depressive symptoms, 17.59% reported their presence, 20.37% anxiety and 20.83% stress. The prevalence of the risk of suicide was 15.74%. In the bivariate analyses, we obtained the association of the risk of suicide with the variables: sexual orientation (p=0.006), marital status (p=0.004), as well as previous attempted suicide, hypnotics/sedatives consumption, symptoms of depression, anxiety and stress, all with a value p<0.001. In the ultimate model, the following entries remained as adjustment variables: marital status (without partner) (p=0.037), previous attempted suicide (p<0.001), stress symptoms (p=0.008), depression symptoms (p=0.008), interaction between the symptoms of stress and depression (p= 0.039) and anxiety symptoms (p=0.366) as adjustment variable. Conclusion: The results of the study are similar to what has been exposed in the scientific literature, mainly on the association between the risk of suicide and psychosocial variables. Regarding the labor variables, although the literature has highlighted its possible influence on the risk of suicide, this association was not obtained in the study at issue. The discoveries reinforce the indispensability of the preparation and implementation of intervention strategies within the hospital institutions for the prevention of this serious event, besides the development of further studies investigating the labor variables.